HR Competency and Financial Literacy Supporting Success as Christian Community-Based Religious Ecotourism Blimbingsari Destination Village - I Ketut Yasa; Ni Made Dwiyana Rasuma Putri; Baskoro Harwindito; Nicko Gana Saputra (International Journal of Travel, Hospitality and Events, 2026)
This study examines how human resource (HR) competency and financial literacy function as foundational pillars in the success of Blimbingsari Tourism Village, a community-based Christian religious ecotourism destination in Bali. Existing research on community-based tourism (CBT) highlights the importance of local participation, governance, and social capital, yet limited attention has been given to how HR competency and financial literacy interact within religious tourism contexts. To address this gap, this study employs a qualitative case study approach, involving in-depth interviews, participant observation, and document analysis with tourism managers, church representatives, financial administrators, and local community members. The findings reveal that HR competency in Blimbingsari is shaped not only by technical skills but also by Christian values, informal learning, and intergenerational mentorship, producing a distinctive competency model rooted in moral integrity, discipline, and service-oriented leadership. Financial literacy is similarly influenced by long-standing church traditions of transparency and stewardship, enabling community members to practice accountable budgeting, record-keeping, and financial reporting despite limited formal education. The integration of HR competency and financial literacy forms a mutually reinforcing system that strengthens community trust, improves tourism service quality, and supports sustainable destination development. However, several challenges persist, including youth migration, uneven digital literacy, fluctuating tourism revenue, and overlapping governance roles between church and village authorities. Overall, this study contributes to the literature on CBT by demonstrating that in religious ecotourism settings, managerial capability and financial competence are embedded within cultural and spiritual frameworks. The findings provide valuable insights for policymakers and practitioners seeking to strengthen community-based tourism governance through culturally grounded capacity-building initiatives.